Wireless Internet telecommunications - Wong, K. Daniel (Artech House mobile communications series, 2005)
This comprehensive book gives you a hands-on understanding of the techniques and architectures being used to provide voice and data services over wireless networks. It serves as a unified "how it works" guide to wireless Internet telecommunications, systematically addressing each of the technological components and how they fit together. You get a clear picture of protocols like RTP for multimedia transport and SIP for session control signaling, and see what's being done to tackle tough challenges in QoS control, mobility management, and security in the wireless environment. The book discusses at length the cutting-edge IP Multimedia Sub-System (IMS) of UMTS to illustrate how each of these crucial components can be successfully implemented in a real-world wireless IP system